Rhinovirus and Influenza Disease Swamedication Information System using the Multi Attribute Decision Making (MADM) method - Husnul Khotimah; Tijaniyah (FT- UNDAR, 2020)
Self-medication, known as self-medication, has now been widely used by people to treat their own diseases without a doctor's prescription. This is because the cost of examining and just consulting a doctor is very expensive for the community. According to the World Health Organization (WHO) self-medication is defined as the selection and use of drugs, including herbal and traditional medicine, by individuals to treat themselves from disease or symptoms of disease. As well as the world of digital information is currently mushrooming in various information systems to provide information to the public in real time. Therefore, the author will make a research on how web-based information systems can provide information to the public about self-medication for coughs and colds, which people often suffer from. The Multi Attribute Decision Making (MADM) method is one of the superior methods for calculating the parameters for drug decisions that can be consumed by the public, making it easier for people to choose the type of medicine according to the disease they are suffering